Affective-prosodic deficits in schizophrenia: profiles of patients with brain damage and comparison with relation to schizophrenic symptoms. Issue 5 (1st May 2001) - Ross, E D; Orbelo, D M; Cartwright, J; Hansel, S; Burgard, M; Testa, J A; Buck, R
Abstract : OBJECTIVE: Although affective prosody seems to be a dominant and lateralised communication function of the right hemisphere, focal lesions of either hemisphere may cause problems with its modulation. When impairment occurs after brain damage, the profiles of affective-prosodic disturbances differ depending on the hemisphere injured. Patients with left brain damage (LBD) improve their performance whereas patients with right brain damage (RBD) do not when the verbal-articulatory demands of the test stimuli are reduced systematically. One of the major arguments for a right hemispheric contribution to schizophrenia has been the documentation of affective prosodic deficits under the assumption that these abnormalities reflect right hemispheric dysfunction. Thus, an essential question to resolve is whether the profile of affective prosodic disturbances in schizophrenia is similar to LBD or RBD, or represents a unique variation. METHODS: Data were collected from four subject groups: 45 chronic, medication-stabilised, schizophrenic patients, 10 patients with focal LBD, nine patients with focal RBD, and 19 controls. All groups were tested on the aprosodia battery, which uses stimuli having incrementally reduced verbal-articulatory demands. Schizophrenic and aphasic symptoms were evaluated using standard assessment tools. RESULTS: For patients with impaired performance on the aprosodia battery, schizophrenic patients were statistically identical to patients with RBD and robustly different from those with LBD. Thirty eight schizophrenic patients (84.4%) were found to have some type of affective prosodic deficit with the predominant pattern indicating, at minimum, right posterior sylvian dysfunction (57.8%). When schizophrenic symptoms and aprosodic deficits were examined using a principal component analysis, affective comprehension and repetition loaded uniquely as separate factors. CONCLUSIONS: The profile of affective-prosodic deficits found in impaired schizophrenic patients is characteristic of RBD, supporting the concept that schizophrenia is a bihemispheric disease process. These deficits may also represent cardinal symptoms of schizophrenia as they are highly prevalent and, except for spontaneous affective prosody, are not associated statistically with traditional clusters of schizophrenic symptoms.